A transformation of cyclopropyl carbene: a highly enantioselective three-component reaction via trapping oxonium ylide by imine. Issue 22 (2nd June 2016) - Li, Mingfeng; Zheng, Qing; Jin, Weifeng; Liu, Shunying; Hu, Wenhao
Abstract: A transformation of cyclopropyl carbene generated from 2-cyclopropyl-2-diazoacetate via oxonium ylide was found by trapping the resulting ylide with imine. The asymmetric three-component reaction of cycloproyl diazoacetates, benzenemethanols and imines afforded a rapid and efficient method to synthesize complex cyclopropane derivatives with excellent diastereoselectivity and enantioselectivity. Graphical abstract: A transformation of cyclopropyl carbene was discovered to promote a highly enantioselective three-component reaction via trapping oxonium ylide by imine.